OPTIMIZATION OF LAND UTILIZATION AS A PHOTO SPOT: STUDENT ENGAGEMENT INITIATIVE IN ENHANCING TOURISM AT KALLWA COFFEE - Tirtoni, Feri; Prapanca, Detak; Surya Perdana, Adika; Navaro, M Saddam (Journal of Social Comunity Services, 2025)
Objective: This project explores the involvement of students from Muhammadiyah University of Sidoarjo in optimizing land use as photo spots at Kallwa Coffee. By designing photo spots intelligently, land that may have previously been overlooked can be optimized for tourism purposes. Areas with strong visual potential can be transformed into attractive photo spots. The aim of this research is to enhance tourism appeal by engaging students in the planning, development, and promotion of the destination.. Method: The research methods include field surveys, collaboration with local communities, and active student involvement.  Results:  The results indicate that student involvement is effective in creating appealing photo spots, raising public awareness, and supporting the growth of tourism at Kallwa Coffee.  Novelty: The photo spots at Kallwa Coffee are not merely aesthetic elements but also serve as a key strategy in enhancing the branding of Kallwa Coffee.